Interventions to decrease short-term peripheral venous catheter-related bloodstream infections: impact on incidence and mortality. Issue 3 (November 2018) - Saliba, P.; Hornero, A.; Cuervo, G.; Grau, I.; Jimenez, E.; Berbel, D.; Martos, P.; Verge, J.M.; Tebe, C.; Martínez-Sánchez, J.M.; Shaw, E.; Gavaldà, L.; et al.
Summary: Background: Short-term peripheral venous catheters are a significant source of healthcare-acquired bloodstream infections and a preventable cause of death. Aim: To assess the effectiveness of interventions applied to reduce the incidence and mortality associated with short-term peripheral venous catheter-related bloodstream infections (PVCR-BSIs). Methods: The intervention included continuous PVCR-BSI surveillance, implementation of preventive measures related to catheter insertion and maintenance in accordance with evidence-based recommendations and the hospital's own data, front-line staff educational campaigns, and assessment of adherence to hospital guidelines by ward rounds. A Poisson regression model was used to estimate the trend of rate per year. Findings: From January 2003 to December 2016, 227 episodes of PVCR-BSI were identified among hospitalized patients at a university hospital. The mean age of patients was 67 years (standard deviation 14 years), 69% were male and the median Charlson score was 3 (interquartile range 2–5). Staphylococcus aureus caused 115 (50.7%) episodes. Thirty-day mortality was 13.2%. After implementation of the intervention, the incidence of PVCR-BSIs decreased significantly from 30 episodes in 2003 (1.17 episodes/10, 000 patient-days) to eight episodes in 2016 (0.36/10, 000 patient-days). The number of episodes caused by S. aureus decreased from 18 episodes in 2003 (0.70/10, 000 patient-days) to three episodes in 2016 (0.14/10, 000 patient-day), and mortality decreased from seven cases in 2003 (0.27/10, 000 patient-days) to zero cases in 2016 (0.00/10, 000 patient-days). Conclusions: Surveillance, implementation of a multi-modal strategy and periodical assessment of healthcare workers' adherence to hospital guidelines led to a sustained reduction in PVCR-BSIs. This reduction had a major impact on S. aureus BSI rates and associated mortality.